PENGARUH CSR DAN KINERJA PERUSAHAAN TERHADAP RISIKO PAJAK - Olivia Gita Melinda; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of CSR and company performance on tax risk. The variables used in this study are the dependent variable (tax risk), the independent variable (CSR), the moderating variable (earnings performance), and the control variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample was taken by using purposive sampling method. Based on the purposive sampling method, the samples obtained were 17 companies for three consecutive years (2017-2019). The analytical method used in this research is OLS regression analysis. The results of this study indicate that CSR has a negative effect on tax risk and earnings performance strengthens the relationship between CSR and tax risk.